2019
DOI: 10.1155/2019/7828909
|View full text |Cite
|
Sign up to set email alerts
|

Submitral Aneurysm in a Patient with a Normal Electrocardiogram

Abstract: A ventricular aneurysm entails well-known risks for the patient such as heart failure, potentially lethal arrhythmias, and systemic embolic phenomena. The submitral or posterolateral ventricular aneurysm is a very rare variety, usually of congenital etiology, which may also have other causes, including ischemic heart disease. The present case is about a 76-year-old male with the antecedent of an acute myocardial infarction 3 years ago. He presented with intermittent, brief, and self-limiting episodes of severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Therefore, the evidence derived from RWSs and their meta-analyses may facilitate validation of conclusions drawn from RCTs and reassure decision-makers that findings can be extrapolated to real-world populations. In 2018, Bai et al addressed this issue by merging OSs and found a reduced risk for major bleeding in AF patients aged ≥65 years ( 34 ). Nevertheless, the enrollment of patients aged 65–74 years may lead to underestimation of major bleeding risk when compared to those aged ≥75 years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evidence derived from RWSs and their meta-analyses may facilitate validation of conclusions drawn from RCTs and reassure decision-makers that findings can be extrapolated to real-world populations. In 2018, Bai et al addressed this issue by merging OSs and found a reduced risk for major bleeding in AF patients aged ≥65 years ( 34 ). Nevertheless, the enrollment of patients aged 65–74 years may lead to underestimation of major bleeding risk when compared to those aged ≥75 years.…”
Section: Discussionmentioning
confidence: 99%